Representation of Women in Leila S. Chudori's Novel Nadira: A Critical Discourse Analysis of Norman Fairclough's Model - Muderika Syamsuddin; Aslan Abidin; Usman Usman (Jurnal Dieksis ID, 2026)
Urgency of this research is to critically examine the representation of women in Leila S. Chudori’s novel Nadira through Norman Fairclough’s Critical Discourse Analysis model in order to uncover underlying gender ideologies and power relations embedded in the text. This study examines the representation of women in Nadira, a novel by Leila S. Chudori, using Norman Fairclough’s Critical Discourse Analysis model. The analysis focuses on various formn of representation that appear through actions, events, states, and mental processes experienced by the female characters in the narrative. This research employes a descriptive qualitative method with reading and note-taking techniques to obtain relevant data from the text. The findings reveal that the representation of women in Nadira is constructed through lexical selection, metaphors, and narrative structures that highlight emotional struggles, power relations, and the psychological experiences of the characters. Through figurative language and vivid depictions of inner turmoil, the novel portrays women as individuals who confront social pressure, emotional instability, and processes of self-meaning. These findings affirm that language in literary works not only conveys stories but also constructs the positions and identities of women within their social contexts.